Wall paintings in the Ukrainian Greek Catholic Church of Christ Lover of Mankind in Zhovkva. History of the absidal scene of The Ascension of Our Lord and its iconographic analysis (selected elements) - Maciej Ireneusz Orzechowski (Sacrum et Decorum, 2013)
The purpose of the article is to present the history of the mural paintings in the Basilian Church of the Sacred Heart of Jesus (today known as Christ Lover of Mankind) in Zhovkva and to perform an iconographic analysis of selected elements of the absidal scene of The Ascension of Our Lord, which contains elements clearly related to the temple’s name.